PENGEMBANGAN CD-ROM MULTIMEDIA INTERAKTIF UNTUK PEMBELAJARAN BAHASA PERANCIS DI SMA - Citra Kandiawan (Jurnal Sora : Pernik Studi Bahasa Asing, 2017)
This research is intented to gather empirical data concerning: (1) the development of interactif multimedia CD-ROM as a media in French language learning; and (2) the students perception in utilisation of interactif multimedia CD-ROM in French language learning. A qualitative and quantitative research approach were used to answer the problem stated in this research. Several tests, questionary, litterature study and interview were applied as an instrument and technic to gather those data. Based on the analysis of the data, we concluded that (1) all the subject proposed in the CD-ROM were arranged to answer the students and teachers needs; (2) both students and teacher were satisfied by using the CD-ROM multimedia interactif in the classroom.